Analysis and Examination of the Role of Cultural Intelligence and Strategic Thinking in Organizations (A Review Study) - Keykhanejad , Mahin; Kord, Khalilollah; Saeedi, Samaneh; Javan , Mehran; Arjmandi , Nadiya (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The present study analyzes and examines the role of cultural intelligence and strategic thinking in organizations. Methods: This research was conducted descriptively using library resources and written information and data. Findings: In recent decades, due to the expansion and creation of various formal and informal organizations and institutions, as well as the increasing growth of relationships and information among these organizations through various means such as virtual spaces, media, etc., competition among them has intensified. Among these, organizations succeed whose leaders possess high cultural intelligence and strategic thinking in specific situations. The fast-paced world of today has confronted organizations, as the fundamental foundations of society, with extensive changes. The findings of the research showed that having cultural intelligence is a vital need for all managers and employees. Successful managers learn well the key to dealing with different national, transnational, and organizational cultures and make the most of their teachings. This type of intelligence improves the understanding and comprehension of intercultural interactions. Conclusion: For an individual to be recognized as culturally intelligent, they must be able to make correct judgments in situations with various perceptions and cues and gain an accurate understanding of that situation. Individuals with higher levels of cultural intelligence have greater control over expressing emotions and physical states, leading to the growth and development of the organization.